2021
DOI: 10.1111/jvs.13010
|View full text |Cite
|
Sign up to set email alerts
|

How does spatial micro‐environmental heterogeneity influence seedling recruitment in ironstone outcrops?

Abstract: Questions: Environmental filters limit the set of potentially coexisting species in plant communities. Paradoxically, some of the world's most biodiverse communities are subjected to strong abiotic filters. We explored how environmental heterogeneity provides conditions for niche segregation in a harsh megadiverse ecosystem, focusing on fine-scale factors that drive seedling recruitment. Due to the environmental stress (mainly nutrient and water scarcity), we expected the prevalence of positive plant interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…Consequently, clonality is expected to be the primary strategy for maintaining viable populations within this group (Porembski, 2006). Although some studies have shown that Velloziaceae species exhibit high germination rates and produce seeds periodically (Dayrell et al., 2021; Stradic et al., 2015; Vieira et al., 2018), we did not find any seedlings of young individuals of Vellozia variabillis or V. tubiflora in the field. Even though these are common and abundant species in Cerrado (Figure S1) and there is information about two other species of Vellozia ( V. leptopetala and V. epidendroides ) exhibiting clonal growth (Jacobi & del Sarto, 2007), there is no record of clonal strategies and information on reproductive strategies for Vellozia variabillis or V. tubiflora in the literature.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Consequently, clonality is expected to be the primary strategy for maintaining viable populations within this group (Porembski, 2006). Although some studies have shown that Velloziaceae species exhibit high germination rates and produce seeds periodically (Dayrell et al., 2021; Stradic et al., 2015; Vieira et al., 2018), we did not find any seedlings of young individuals of Vellozia variabillis or V. tubiflora in the field. Even though these are common and abundant species in Cerrado (Figure S1) and there is information about two other species of Vellozia ( V. leptopetala and V. epidendroides ) exhibiting clonal growth (Jacobi & del Sarto, 2007), there is no record of clonal strategies and information on reproductive strategies for Vellozia variabillis or V. tubiflora in the literature.…”
Section: Discussioncontrasting
confidence: 78%
“…& Schult.f species, yet at that moment, no group member could promptly answer the question. Although it is possible to find seedlings of this species in the field (Dayrell et al, 2021), we were unable to observe them in the ground layer across the 920 sampling units (1 m 2 ) where we were working. Nor could we retrieve this information by revisiting numerous other field expeditions conducted in Cerrado grasslands dominated by Vellozia spp.…”
Section: Introductionmentioning
confidence: 98%